Integration of SuperCam based chemical imaging and clustering to correlate geochemistry and mineralogy in heterogeneous samples - García-Gómez, Laura; Población, Iraxte; Delgado-Pérez, Tomás; Laserna-Vázquez, José Javier; Velasquez, Marizu; Porizka, Pavel; Buday, Jakub; Kaiser, Josef; Lobato, Álvaro; Casado, Ana I.; Taravillo, Mercedes; Madariaga, Juan Manuel; et al. (Nature, 2025)
Peridotites are ultramafic rocks whose mineralogical diversity makes them suitable case studies for testing analytical methodologies. In this study, a peridotite sample from the Ronda massif (Málaga, Spain) was examined demonstrating a practical methodology for distinguishing geochemically distinct regions within complex lithologies. The sample was analyzed using a multi-instrumental approach combining laser-induced breakdown spectroscopy (LIBS), micro-energy dispersive X-ray fluorescence (µ-EDXRF), and Raman spectroscopy, all of them integrated in the Perseverance rover payload. LIBS and µ-EDXRF were used to assess elemental composition and spatial distribution across the sample, whereas Raman spectroscopy confirmed the presence of mineral phases such as, olivine, pyroxenes, and chromiferous spinels in specific regions. Elemental LIBS ratios such as Mg# and Cr# further supported the identification of compositional variations related to mineral phases. Spectral LIBS data were processed using k-means clustering to segment geochemical zones and detect spatial trends. This integrated spectroscopic and statistical approach enables interpretation of ultramafic rock complexity and offers an efficient framework for planetary exploration under mission constraints.
Keywords: Espectroscopía de plasma inducido por láser; Algoritmos computacionales; Aprendizaje automático (Inteligencia artificial); Planetas - Exploración; LIBS; Mapping; K-means; Planetary exploration